An examination of the ocular surface parameters of patients with non-exophthalmic Graves disease (Annals of Medical Research, 2023)
Aim: To evaluate patients with non-exophthalmic Graves Disease (GD) in respect of ocular surface and tear film abnormalities, central corneal thickness (CCT) and central corneal epithelial thickness (CCET) values.Materials and Methods: This prospective research included non-exophthalmic patients referred to the ophthalmology outpatient clinic because of GD in 2023. In all patients, dry eye was evaluated with tear break-up time (TBUT) and the Schirmer test, and the CCT and CCET values were measured using Spectral-Domain anterior segment optical coherence tomography (AS-OCT).Results: The data of a group of 26 patients with GD, comprising 14 males and 12 females with a mean age of 43.27 ± 15.25 years were compared with a control group of 26 healthy individuals, comprising13 males and 13 females with a mean age of 41.69 ± 13.4 years. No statistically significant difference was determined between the two groups in respect of age and gender (p=0.694, p=0.781 respectively). The TBUT values of both eyes were statistically significantly lower in the GD patients compared to the control group (p0.05).Conclusion: The findings suggest that tear film abnormalities occur in GD patients before Graves orbitopathy (GO) develops or even in inactive GO. Therefore, it is important that the ocular surface is evaluated regularly in GD patients, irrespective of GO status.
Keywords: Graves orbitopathy; Inactive Graves orbitopathy; Dry eye; Central corneal thickness; Central corneal epithelial thickness